Bioethanol Production from Spent Sugar Beet Pulp—Process Modeling and Cost Analysis - Damjan Vučurović; Bojana Bajić; Vesna Vučurović; Rada Jevtić-Mučibabić; Siniša Dodić (Fermentation, 2022)
Global economic development has led to the widespread use of fossil fuels, and their extensive use has resulted in increased environmental pollution. As a result, significantly more attention is being paid to environmental issues and alternative renewable energy sources. Bioethanol production from agro-industrial byproducts, residues, and wastes is one example of sustainable energy production. This research aims to develop a process and cost model of bioethanol production from spent sugar beet pulp. The model was developed using SuperPro Designer® v.11 (Intelligen Inc., Scotch Plains, NJ, USA) software, and determines the capital and production costs for a bioethanol-producing plant processing about 17,000 tons of spent sugar beet pulp per year. In addition, the developed model predicts the process and economic indicators of the analyzed biotechnological process, determines the share of major components in bioethanol production costs, and compares different model scenarios for process co-products. Based on the obtained results, the proposed model is viable and represents a base case for further bioprocess development.